Pengaruh Tunjangan Kinerja dan Disiplin Kerja Terhadap Kinerja Pegawai di Kantor Kecamatan Panjang Kota Bandar Lampung - Hendri Dunan; Sindi Yuna Sari (Jurnal EMT KITA, 2023)
The study aims to identify merit pay and labor discipline issues affecting employee performance in the Panjang district of Bandar Lampung. As a research method, descriptive and quantitative field research is used. Research data were collected through a questionnaire completed by 30 respondents. The study concluded that performance bonuses have a significant impact on employee performance, as indicated by the X1 significance level analysis. This is less than a value (0.000 1.984). Furthermore, work discipline also has a large effect on employee performance, with the X2 significance level being less than a value (0.259 1.984). Combining performance bonuses and work discipline affects employee performance, and the calculated Fcount of 23,336 is greater than the Ftable of 3,354. The research hypothesis is accepted. A correlation coefficient (r) of 0.796 indicates a valid relationship between the independent and dependent variables. However, fluctuating performance pay, and work discipline accounted for only 63.4% of his variability in employee performance, with the remaining 36.6% of his being influenced by other factors not investigated in this study.